2021
DOI: 10.3389/fimmu.2021.656090
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Autoantibody Induced by Bacterial Biofilm Conserved Components Aggravates Lupus Nephritis

Abstract: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with multiple autoantibody production and often affects the kidneys, known as lupus nephritis. However, the mechanism underlying lupus nephritis development is unclear. Biofilms that protect bacteria from stress are ubiquitous in almost every environment. Here, we identified that a conserved peptide (HU1) derived from DNABII proteins, one of major bacterial biofilm components, was specifically recognized by sera from about 47% patients with SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Biofilms are considered to be a membrane in which the bacterial community produces an extracellular matrix and wraps itself (53), which can protect bacteria from the host immune response (54) and enable bacteria to develop drug resistance (55). The main structure of biofilms is amyloid protein rich in b-folding, which is associated with human autoimmune diseases (56)(57)(58). Curli fibrils in Salmonella enterica serovar Typhimurium (S. Typhimurium) amyloid could combined to the DNA in bacterial, and these complexes could promote biofilm formation, also contributing to SLE pathogenesis (57).…”
Section: The Pathogenic Role Of Bacterial Biofilmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biofilms are considered to be a membrane in which the bacterial community produces an extracellular matrix and wraps itself (53), which can protect bacteria from the host immune response (54) and enable bacteria to develop drug resistance (55). The main structure of biofilms is amyloid protein rich in b-folding, which is associated with human autoimmune diseases (56)(57)(58). Curli fibrils in Salmonella enterica serovar Typhimurium (S. Typhimurium) amyloid could combined to the DNA in bacterial, and these complexes could promote biofilm formation, also contributing to SLE pathogenesis (57).…”
Section: The Pathogenic Role Of Bacterial Biofilmsmentioning
confidence: 99%
“…The above two studies suggest that bacterial proteins that interact with DNA may cause loss of immune tolerance to autoantigens and induce the production of autoantibodies, leading to SLE pathogenesis. Interestingly, a recent study by Fu et al (58) suggested that DNABII proteins interacting with DNA in biofilms may not directly contribute to anti-dsDNA production but other mechanisms may be involved. Sera from patients with SLE specifically recognize the DNAB II protein-derived HU1 peptide in bacterial biofilms.…”
Section: The Pathogenic Role Of Bacterial Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cross-reactivity of P4HB with anti-DENV nonstructural protein 1 (NS1) antibodies may play a role in DENV infection-induced autoimmunity [ 108 ]. In some SLE patients, antibodies against the HU1 bacterial peptide recognized P4HB as an autoantigen on the membrane of renal cells, inducing lupus nephritis [ 109 ]. Thus far, polymorphisms in P4HB have not been related to complex diseases.…”
Section: Discussionmentioning
confidence: 99%